High performance electrospun PVdF‐HFP/SiO2 nanocomposite membrane electrolyte for Li‐ion capacitors. Issue 32 (16th April 2017) - Solarajan, Arun Kumar; Murugadoss, Vignesh; Angaiah, Subramania
ABSTRACT: Electrospun poly[(vinylidene fluoride)‐ co ‐hexafluoropropylene]/silica (PVdF‐HFP/SiO2 ) nanocomposite polymer membranes (esCPMs) were prepared by incorporating different weight percentages of SiO2 nanoparticles onto electrospun PVdF‐HFP by electrospinning technique. The surface morphology of electrospun PVdF‐HFP nanocomposite membranes was characterized by scanning electron microscopy. The effect of SiO2 nanoparticles incorporation onto electrospun PVdF‐HFP polymer membranes (esPMs) has been studied by XRD, DSC, TGA, and tensile analysis. The electrospun PVdF‐HFP/SiO2 based nanocomposite membrane electrolytes (esCPMEs) were prepared by soaking the corresponding esCPMs into 1 M LiPF6 in EC:DMC (1:1 vol/vol %). The ionic conductivity of the esCPMEs was studied by AC‐impedance studies and it was found that the incorporation of SiO2 nanoparticles into PVdF‐HFP membrane has improved the ionic conductivity from 1.320 × 10 −3 S cm −1 to 2.259 × 10 −3 S cm −1 . The electrochemical stability of the esCPME was studied by linear sweep voltammetry studies and it was found to be 2.87 V. Finally, a prototype LiCo0.2 Mn1.8 O4 //C Li‐ion capacitor (LIC) cell was fabricated with esCPME, which delivered a discharge capacitance of 128 F g −1 at the current density of 1 A g −1 and retained 86% of its discharge capacitance even after 10, 000 cycles. These results demonstrated that the esCPMEs could be used as promising polymer membrane electrolyte for LICs. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45177. Abstract :